Fungsi-Fungsi Aparat Pemerintah dalam Mewujudkan Tujuan Negara - Roy Saputra (UIN Sunan Kalijaga Yogyakarta, 2017)
To achieve the objectives of the state, the government has the authority distributedto the means of state power, so that each sector of the state goal can be simultaneouslydone in order to achieve and realize the goals of the state. In order to prosper thecommunity, there is a close legal relationship (rechtsbetrekking) between the governmentand its people. In other words the government has an obligation to provide services to thepublic (public service). With this public service function, it means that the governmentdoes not only implement the legislation alone (executive function), but also increases theobjectives of the law itself. Therefore the government is entitled to create a concrete legalnorm intended to realize the legislative objectives created by the legislative power. Thisfunction is called the state administration function. While officials who perform thefunctions of state administration which incidentally is captured by government officials iscalled administrative tools.